Post-bubble blues : how Japan responded to asset price collapse - Bayoumi, Tamim A.; Collyns, Charles (International Monetary Fund, 2000)
Japans accounts for over half the output of the Asian region, but for muchof the 1990s its economy was virtually stagnant, and it is only just emerging from its worst recession since the Second World War.